Development of a creative collaborative with critical experience learning model to improve technological pedagogical and content knowledge of preservice chemistry teachers - Mashuri, Mohan Taufiq; Sutoyo, Suyatno; Azizah, Utiya (Nurture, 2024)
Purpose: This research aims to produce a valid, practical and effective 3CEL learning model which is an abbreviation of creative collaborative with critical experience learning to improve the Technological Pedagogical and Content Knowledge (TPACK) of preservice chemistry teachers. Design/Methodology/Approach: This is development research that was carried out in four main stages: 1) preliminary stage (literature and field study), 2) development stage (hypothetical model or prototype), 3) validation stage and 4) model implementation stage (final 3CEL model). The data collection techniques used in this research are validation, observation, test and questionnaires. Findings: The final 3CEL learning model along with supporting learning tools and validated TPACK measurement instruments. The results of validation showed that the 3CEL learning model along with its supporting learning tools and TPACK measurement instruments were very valid and reliable. The results of the 3CEL learning model implementation in the experimental class and the control class proved that the 3CEL learning model was very effective in improving the TPACK abilities of preservice chemistry teachers. Conclusion: This research produced a new learning model (3CEL) that is valid, practical and effective in improving the TPACK of preservice chemistry teachers. The syntax of the resulting 3CEL learning model consists of five phases: 1) orientation, 2) collaborative planning, 3) presenting, 4) simulation and 5) reflection based on critical experience.